Acidity control of the oxidation reactions induced by non-thermal plasma treatment of aqueous effluents in pollutant abatement processes - Addou, Ahmed; Moussa, D; Abdelmalek, F; Benstaali, B; Hnatiuc, E; Brisset, JL (Eur Phys J Appl Phys, 2005)
The acid properties of a non-thermal plasma in humid air (e.g., a gliding arc device) induced in an aqueous solution may deeply affect the efficiency of the matching oxidising proper- ties, especially when the aqueous targets involve organic solutes. Hence, their oxidation rate may be strongly modified. A series of buffers is proposed to control the pH of aqueous target for at least one-hour treatments. The selected acid-base systems were selected for their inertia towards oxidation reaction, to cover a very large range of acidity. The reported results are essential from both fundamental and applied points of view. They first al- low the acute controlling of the degradation rate of organic compounds. They also enable estimat- ing the efficiency of the gliding arc process in pollutant abatement pollutants, which is one on the main applications of the gliding arc treatments in environmental applications. Besides, they allow getting reliable data on the bactericidal effect of the plasma treatment s, which are a merging appli- cation of the electric discharges.